Magnitude of Psoriasis and Its Associated Factors, and Quality of Life of Psoriasis Patients among Patients Who Attend Dermatology Clinic at Tibebe Ghion Comprehensive Specialized and Addis Alem Primary Hospitals, North West Ethiopia, 2022: Institution-Based Cross-Sectional Study - Wosen Ketema; Solomon Ketema Bogale; Eyob Ketema Bogale (Dermatology Research and Practice)
Background. Psoriasis is a common immune-mediated papulosquamous inflammatory skin disease characterized by well-demarcated, erythematous silvery scaly plaques. Prevalence rates of psoriasis showed a worldwide variation and have been reported to range between 0.09% and 5.1%. It has been associated with several intrinsic as well as extrinsic factors and has a detrimental effect on health-related quality of life. Studies on the burden, factors associated with it, and quality of life of psoriasis are limited in the study area. Objectives. To assess the magnitude, factors associated with it, and quality of life of psoriasis patients. Methods. Institution-based cross-sectional study was conducted among patients who attend dermatology clinics at Tibebe Ghion comprehensive specialized and Addis Alem primary hospitals from June 8 to September 5, 2022. Systematic random sampling was applied to select study participants until the sample size (318) was fulfilled. A structured interviewer-administered questionnaire was used to collect data. Collected data were coded and entered into EPI data version 3.1 and then exported to SPSS version 27 for analysis. Descriptive statistics and logistic regression analysis were done. Result. The mean age of study participants was 22.5 with a standard deviation (SD) of 18.2 years. The proportion of psoriasis was 5.3% with a 95% CI (3.1%, 8.4%). Stressful life events (AOR = 3.32, 95% CI (1.12, 9.86)) and alcohol consumption (AOR = 3.73, 95% CI (1.03, 13.51)) were significantly associated with psoriasis. Seven (41.2%) psoriasis patients had a large effect on their quality of life. The mean dermatology quality of life index (DLQI) was 9.82. Conclusion. The proportion of psoriasis in this study was comparable to earlier international and Ethiopian studies, but greater than studies from other African countries. Stressful life events and alcohol consumption were significantly associated with psoriasis. The majority of psoriasis patients had a large negative effect on their quality of life.